In silico design of novel multifunctional hybrid materials composites based on mordenite combined with ionic liquids and silver clusters. Unveiling new processes of capture, separation and elimination of CO2, NO, NO2, H2S, and CH3SH - Izquierdo Soto, Rodolfo Enrique (Universidade Estadual Paulista (Unesp), 2023)
The project focused on reducing CO2, H2S, CH3SH, SOx, and NOx emissions by developing new composites that capture and/or convert these pollutants. This project had an extensive and ambitious scope, we emphasize that combining the potentialities of Ionic liquids based on functionalized imidazolium cations (Im-ILs) and zeolites type mordenites, new composites with exceptional capacities can be obtained for gas capture. Im-ILs inside the zeolite cavities may introduce interesting modifications affecting the composite's physical and/or catalytic behavior
Desenho in silico de novos materiais híbridos multifuncionais à base de mordenita combinados com líquidos iónicos e clusters de prata. Desvelando novos processos de captura separação e eliminação de CO2, NO, NO2, H2S e CH3SH
Objectives 1. Study the interaction of the Im-ILs ion-pairs ([M]Cl, Scheme 2) with Na-MOR and H-MOR models to understand the [M]-MOR formation via EI (see reaction 2 in Scheme 2). 2. Analyze the main critical points in conformational PESs for [M]-MOR models to propose confined cation conformational traps into MOR ([M]HB-MOR, [M]-MOR, and TS1-MOR (gas-capture molecular switches). 3. Determine activation parameters (ΔE‡ and ΔH‡) and thermodynamic functions (ΔEisom and ΔHisom) for the rotational isomerization from ([M]HB-MOR (i.e., CO2-CSOFF or R-SH-CSOFF) to ([M]-MOR (i.e., CO2-CSON or R-SH-CSON). 4. Study the interaction of H2, O2, N2, H2S, R-SH, CO2, CH4, C2H6, and C3H8 with the [M]HB-MOR and [M]-MOR to establish capture mechanisms of CO2, H2S and RSH based on conformational traps into MOR. 5. Study the adsorption isotherms and reliable values of external stimuli for the molecular recognition switch of CO2, H2S, and CH3SH on [M]-MOR using Grand Canonical Monte Carlo (GCMC) simulations. 6. Study the diffusion of H2, O2, N2, H2S, R-SH, CO2, CH4, C2H6, and C3H8 within the [M]-MOR models by using classical Molecular Dynamic classical (DM). 7. Assess using DFT the structural, electronic and energetic properties of the [Agn]+, [Agn]0 clusters (n from 2 to 10). 8. Study the interaction of H2, O2, N2, CO, CO2, NO, N2O, NO2, NH3, CH4, C2H6, and C3H8 with the clusters [Agn]+, [Agn]0. 9. Study the interaction of clusters [Agn]+, [Agn]0 with models of [M]-MOR to design new mechanisms for regulated admission and rejection of silver motifs. 10.Study the interaction of H2, O2, N2, CO, CO2, NO, N2O, NO2, CH4, C2H6, and C3H8 with silver-loaded [M]-MOR materials in an environment with NH3 11. Study the interaction of H2, O2, N2, CO, CO2, NO, N2O, NO2, CH4, C2H6, and C3H8 with silver-loaded [M]-MOR materials.12. Study the adsorption isotherms and reliable values of external stimuli for the molecular recognition switch of [Agn]+, [Agn]0 on [M]-MOR using Grand Canonical Monte Carlo (GCMC) simulations. 13. Study the diffusion of [Agn]+, [Agn]0 within the [M]-MOR models by using classical Molecular Dynamic classical (DM). 14. Study with ONIOM-DFT the main TWC reactions using catalysts based on silver-loaded [M]-MOR materials. 15. Synthesize the best candidates for multifunctional materials based on silver-loaded [M]-MOR and ceramic fibers embedded with silver nanoparticles by an unprecedented theoretical-experimental cooperative association. Bolsa: Edital PROPe 13/2022/ UNESP
Keywords: Zeólita; Líquidos iônicos; Mordenita; DFT